CARE TECHNOLOGIES IN OBSTETRIC NURSING: CONTRIBUTION FOR THE DELIVERY AND BIRTH - Micheliana Rodrigues Duarte; Valdecyr Herdy Alves; Diego Pereira Rodrigues; Kleyde Ventura de Souza; Audrey Vidal Pereira; Mariana Machado Pimentel (Universidade Federal do Paraná, 2019)
Objective: to identify the care technologies used by obstetric nurses in a Normal Birth Center. Method: a descriptive study, performed at the Normal Birth Center of a maternity hospital in the city of Rio de Janeiro, with eighteen obstetric nurses, using semi-structured interviews between June and September 2016. The data collected were submitted to thematic type content analysis. Result: the obstetric nurse uses non-pharmacological methods such as a spray bath, massage, Swiss ball, horse, aromatherapy, music therapy, free movement, warm environment and presence of the companion, as care practices together with the women. Conclusion: the use of care technologies allows obstetric nurses to valorize humanized practices in the context of the delivery and birth